ABCA1 overexpression worsens colorectal cancer prognosis by facilitating tumour growth and caveolin‐1‐dependent invasiveness, and these effects can be ameliorated using the BET inhibitor apabetalone. Issue 10 (17th September 2018) - Aguirre‐Portolés, Cristina; Feliu, Jaime; Reglero, Guillermo; Ramírez de Molina, Ana
Abstract : At the time of diagnosis, 20% of patients with colorectal cancer present metastasis. Among individuals with primary lesions, 50% of them will develop distant tumours with time. Therefore, early diagnosis and prediction of aggressiveness is crucial for therapy design and disease prognosis. Tumoral cells must undergo significant changes in energy metabolism to meet increased structural and energetic demands for cell proliferation, and metabolic alterations are considered to be a hallmark of cancer. Here, we present the ATP‐binding cassette transporter (ABCA1), a regulator of cholesterol transport, as a new marker for invasion and colorectal cancer survival. ABCA1 is significantly overexpressed in patients at advanced stages of colorectal cancer, and its overexpression confers proliferative advantages together with caveolin‐1 dependent‐increased migratory and invasive capacities. Thus, intracellular cholesterol imbalances mediated by ABCA1 overexpression may contribute to primary tumour growth and dissemination to distant locations. Furthermore, we demonstrate here that increased levels of apolipoprotein A1 (APOA1), a protein involved in cholesterol efflux and high‐density lipoprotein constitution, in the extracellular compartment modulates expression of ABCA1 by regulating COX‐2, and compensate for ABCA1‐dependent excessive export of cholesterol. APOA1 emerges as a new therapeutic option to inhibit the promotion of colorectal cancer to metastasis by modulating intracellular cholesterol metabolism. Furthermore, we propose apabetalone, an orally available small molecule that is currently being evaluated in clinical trials for the treatment of atherosclerosis, as a new putative therapeutic option to prevent colorectal cancer progression by increasing APOA1 expression and regulating reverse transport of cholesterol. Abstract : ABCA1 overexpression leads to increased proliferation, epithelial‐to‐mesenchymal transition and promotes migration and invasion by regulating Caveolin‐1 stability. In each of these steps of tumorigenesis, apabetalone can regulate the expression of the cholesterol transporter, thereby acting as a bona fide inhibitor of colorectal cancer invasiveness.